PANDANGAN HAMKA TENTANG KONSEP JIHAD DALAM TAFSIR AL-AZHAR - Slamet Pramono (Dialogia, 2015)
Abstract: Jihad is an integral part of Islamic discourse since the early days of contemporary Muslims. Talks about jihad and concepts that had explained, they little bit change and shift its contents according to the context and environment of each thinker. In explaining jihad, it depends on customize with shades and nuances that the commentators have. The different styles of interpretations, will give different interpretations among others. The object of this research is thematic study focused on Al-Qur-an in depth to get a clue in knowing HAMKA views about the concept of jihad in Tafsir al-Azhar. In this Tafsir, HAMKA explained that the meaning of jihad is working hard, serious or struggling. HAMKA gave the primary meaning of jihad is hard working, conscientious, do not know the omission, night and day, evening and morning. The aims of Jihad are Religion development and the path of Allah upright with calyx. Struggling with emphasis on power, possessions, and if necessary with the soul. Keywords: Jiha>d Akbar, Tafsir Al-Azhar dan Kesungguhan